2001
DOI: 10.1007/s00497-001-0108-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression during flowering in apomeiotic mutants of Medicago spp.: cloning of ESTs and candidate genes for 2n eggs

Abstract: Mutants showing features of apomixis have been documented in alfalfa (Medicago sativa L.), a natural outcrossing sexual species. A differential display of mRNAs that combines cDNA-AFLP markers and bulked segregant analysis was carried out with the aim of selecting expressed sequence tags (ESTs) and cloning candidate genes for apomeiosis in mutants of alfalfa characterized by 2n egg formation at high frequencies. The approach enabled us to select either mutant- or wild type-specific transcript derived-fragments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…cDNA-AFLP (Bachem et al, 1996) has proved the most popular procedure because of its ability to detect differentially expressed genes. It has good reliability and sensitivity, and correlates well with Northern analysis (Durrant et al, 2000;Jones et al, 2000;Barcaccia et al, 2001;Donson et al, 2002;Cnudde et al, 2003). Compared to microarray and GeneChip technologies (Reijans et al, 2003) the reproducibility is very high.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…cDNA-AFLP (Bachem et al, 1996) has proved the most popular procedure because of its ability to detect differentially expressed genes. It has good reliability and sensitivity, and correlates well with Northern analysis (Durrant et al, 2000;Jones et al, 2000;Barcaccia et al, 2001;Donson et al, 2002;Cnudde et al, 2003). Compared to microarray and GeneChip technologies (Reijans et al, 2003) the reproducibility is very high.…”
Section: Introductionmentioning
confidence: 84%
“…Gene expression-based techniques combined with differential display should extend our knowledge of apomixis and some progress has been made in this direction by studying the gene expression of model system mutants in Arabidopsis and rice, where some genes that resemble features of apomixis have been cloned and characterized: SPL (Schiefthaler et al, 1999), NZZ (Yang et al, 1999), SERK (Schmidt et al, 1997;Hecht et al, 2001), LEC1, LEC2 and PKL (Ogas et al, 1999), FIS1 (or MEA), FIS2 and FIS3 (or FIE) (Ohad et al, 1996;Grossniklaus and Schneitz, 1998;Kiyosue et al, 1999;Luo et al, 1999;Vielle-Calzada et al, 1999). Comparative gene expression studies have been carried out during the early stages of apomictic and sexual embryo sac development in Panicum maximum (Chen et al, 1999), Brachiaria species (Leblanc et al, 1997;Dusi, 2001;Rodrigues et al, 2003), Pennisetum (Vielle-Calzada et al, 1996Jessup et al, 2003), Paspalum (Pessino et al, 2001), Poa pratensis (Albertini et al, 2003) and apomeiotic mutants of Medicago falcata (Barcaccia et al, 2001). However, most were based on subtractive hybridization techniques and isolated only a few genes to which, disappointingly, no clear function could be assigned.…”
Section: Introductionmentioning
confidence: 99%
“…Apomictic seed production is highly variable in this species and is characterized by complex fertilization scenarios between reduced and unreduced male and female gametes (Matzk et al 2001). Furthermore, H. perforatum shows a number of traits characteristic of hybridity, including variability in morphology and chemical compound production, meiotic abnormalities (e.g., lagging chromosomes), elevated pollen grain sterility, parthenogenic development of unreduced egg cells and pseudogamy (Matzk et al 2001;Barcaccia et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mutant analysis and molecular tagging of 2n egg and 2n pollen formation have shown that 2n gamete production is under polygenic control. This finding, however, is dependent on environmental conditions (Hermsen 1984; Parrott and Smith 1986;Calderini and Mariani 1997;Tavoletti et al 2000;Barcaccia et al 2000Barcaccia et al , 2001. In the genus Populus, 2n pollen has been detected in P. canescens (Seitz 1954) and P. deltoids (Bradshaw and Stettler 1993).…”
Section: Discussionmentioning
confidence: 99%